Cardiotrophin-1: A multifaceted cytokine. Issue 5 (October 2015) - López-Yoldi, Miguel; Moreno-Aliaga, María J.; Bustos, Matilde
Highlights A detailed overview of the biological actions of cardiotrophin-1 is given. The role of cardiotrophin-1 in metabolism is briefly reviewed. The protective role of cardiotrophin-1 in different organs is presented. The review discusses the physiological role of CT-1 in different organs.